Resuscitation room blood alcohol concentrations: one-year cohort study. Issue 11 (27th October 2008) - Touquet, R; Csipke, E; Holloway, P; Brown, A; Patel, T; Seddon, A J; Gulati, P; Moore, H; Batrick, N; Crawford, M J
Abstract : Objective: To clarify the relationship between presenting clinical condition and blood alcohol concentration (BAC) among adult patients admitted to a resuscitation room (RR) of an emergency department (ED) in order to help guide clinical practice. Method: Single-site prospective cohort study of all patients admitted to the RR of an inner-city hospital over a one-year period. The study sample comprised all those aged 16 years and over from whom a blood sample was taken, with BAC (results not known to ED staff), pathology by International Classification of Diseases (ICD) version 10 coding, injury severity score for trauma, return visit to hospital and mortality during the subsequent 6-month period, being recorded. Results: 291 (15%) of 1908 presentations had a positive BAC (ie, BAC >10 mg/100 ml) ranging from 11 to 574 mg/100 ml, of which almost 40% were over 240 mg/100 ml (ICD-10 code Y90.8). In addition to collapse from alcohol/drugs, almost half of those presenting following self-harm or assault had a positive BAC. Those with a positive BAC had a higher rate of ED re-attendance in the following 6 months. 10% of all presentations were due to trauma. Conclusion: The following five presentations to the RR are associated with a positive BAC: collapse from alcohol/drugs, self-harm, trauma, gastrointestinal bleeding (ICD-10 code K92.2) and non-cardiac chest pain (ICD-10 code R07). Patients with a positive BAC demonstrate a very wide range of pathology, some with severe levels of misuse. This highlights the opportunity for prompt feedback when sober, to ensure all is done to encourage patients to contemplate change in order to reduce re-attendance.